Evaluasi Pengendalian Internal Piutang Usaha dalam Upaya Meminimalisir Risiko Piutang Tak Tertagih Pada Cv. Anugrah Jaya Motor - Salma Maria Regina Mano; Diana Zuhroh (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
This research aims to evaluate internal control over trade receivables in an effort to minimize the risk of bad debts at CV. Anugrah Jaya Motor in Surabaya. The research results show that the internal control system implemented is still weak and not in accordance with good accounting principles. First, the provision of credit is carried out by the sales department without credit worthiness analysis or authorization from management, thereby increasing the risk of bad debts and potential fraud. Second, the lack of separation of duties between the sales, accounting and cash receipts departments results in weak internal controls, as well as opening up opportunities for misuse and inaccuracies in financial reports. Third, even though there is an internal control system, its implementation is not yet effective because the entire process from granting credit to receiving payments is carried out by one department. To minimize risks, CV. Anugrah Jaya Motor needs to establish a credit function that is separate from sales, apply 5C analysis in providing credit, and separate the functions of billing, cash receipts and accounting records. With an adequate internal control system and clear separation of duties, it is hoped that bad debts can be minimized and financial reports become more reliable.